Capturing the Perceived Phantom Limb through Virtual Reality. (5th September 2016) - Rogers, Christian; Lau, Jonathan; Huynh, Denver; Albertson, Steven; Beem, James; Qian, Enlin
Abstract : Phantom limb is the sensation amputees may feel when the missing limb is still attached to the body and is still moving as it would if it still existed. Despite there being between 50 and 80% of amputees who report neuropathic pain, also known as phantom limb pain (PLP), there is still little understanding of why PLP occurs. There are no fully effective long-term treatments available. One of the struggles with PLP is the difficulty for amputees to describe the sensations of their phantom limbs. The sensations may be of a limb that is in a position that is impossible for a normal limb to attain. The goal of this project was to treat those with PLP by developing a system to communicate the sensations those with PLP were experiencing accurately and easily through various hand positions using a model arm with a user friendly interface. The system was developed with Maya 3D animation software, the Leap Motion input device, and the Unity game engine. The 3D modeled arm was designed to mimic the phantom sensation being able to go beyond normal joint extensions of regular arms. The purpose in doing so was to obtain a true 3D visualization of the phantom limb.